The effectiveness of picture chart media on students’ English vocabulary - Novanie Sulastri (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2011)
The study is aimed at investigating the effectiveness of using picture chart media on students’ English vocabulary. The study belonged to pre-experimental study by applying counterbalance procedure to collect the data. The study was conducted at the class VII-5 at the SMPN 1 Palangka Raya. The number of the sample was 40 students. This study was restricted to focus on teaching vocabulary especially in classification of vocabulary. To answer the research problem, the t test for correlated was applied. The research findings showed that teaching vocabulary by using picture chart media gives effect toward the seventh grade students’ English vocabulary. The mean score of posttest reached higher score than the mean score of pretest (X=57.105 < Y=84.79). Meanwhile, t test formula using manual calculation showed that the t observed was 15.036. By comparing the t observedwith the t table, it was found that the t observed was higher than t tableat 5% level significance or t observed =15.036 > t table =2.021.